Supportive care improves self-care management and knowledge of patients with heart failure and diabetes mellitus - Philippou, Katerina; Vouri, N.; Malaktou, A.; Samara, A. P.; Kyriakou, M.; Avgousti, Sotiris; Lambrinou, Ekaterini (My University, 2024)
Introduction Heart failure (HF) and diabetes mellitus (DM) most of the times occur together, aggravating patients’ outcomes and the interaction of the two conditions, which is complex, make the application of effective management programs necessary, in order to improve patients’ outcomes. Purpose The aim of the current study was to evaluate the effectiveness of an individualized supportive care management program in patients with HF and DM, in order to improve patients’ self-management compared to the ‘usual’ care. Methods The current study is a sub-analysis of the randomized clinical trial named ‘SupportHeart’ using pragmatic methodology. It was consisted by the intervention group (IG) and the control group (CG). The study investigated the patients for a period of one year at 5 time points (in baseline, 1 month, 3 months, 6 months and 1 year). Self –care management was measured with the Greek versions of two tools: the ‘Self-care of Heart Failure Index’ (Gr-SCHFI) and the ‘European Heart Failure Self-Care Behavior Scale’ (Gr9EHFScBS). Linear Mixed Models Effects (LMME) were also used.
Keywords: physical activity; diabetes mellitus; heart failure; self caree